Recognition of familiarity on the basis of howls: a playback experiment in a captive group of wolves - Palacios, Vicente; Font, Enrique; Márquez, Rafael; Carazo, P. (Behaviour, 2015)
Playback experiments were conducted with a pack of captive Iberian wolves. We used a habituation–discrimination paradigm to test wolves’ ability to discriminate howls based on: (1) artificial manipulation of acoustic parameters of howls and (2) the identity of howling individuals. Manipulations in fundamental frequency and frequency modulation within the natural range of intra-individual howl variation did not elicit dishabituation, while manipulation of modulation pattern did produce dishabituation. With respect to identity, across trials wolves habituated to unfamiliar howls by a familiar wolf (i.e., no direct contact, but previous exposure to howls by this wolf), but not to unfamiliar howls from unfamiliar wolves (i.e., no direct contact and no previous exposure to howls by these wolves). Modulation pattern seems to be an important bioacoustic feature for individual recognition. Overall, our results provide the first experimental evidence that wolves can discriminate individuals based on the acoustic structure of their howls. Sound analysis and playback test training and equipment was funded by the Ministerio de Ciencia e Innovación (Spain), projects TATANKA CGL2011-25062, CGL2010-09700 and ACOURA CGL2008-04814 (PI R. Márquez). This is scientific paper no. 4 from the Iberian Wolf Research Team (IWRT). Peer Reviewed